Antipodean agricultural and resource economics at 60: Trends in topics, authorship and collaboration1. (13th June 2016) - Polyakov, Maksym; Gibson, Fiona L.; Pannell, David J.
Abstract : This study presents results of an analysis of 1060 academic articles published in the Australian Journal of Agricultural Economics and the Australian Journal of Agricultural and Resource Economics from 1957 to 2015. Trends in research topics over time identified by the study include a decline in research on agricultural topics offset by growth in publications related to natural resources, the environment, trade, food and international development. Other trends include an increase in the average number of co‐authors on each paper, a gradual increase in authorship by females, changes in the shares of top contributing institutions, increases in collaboration between institutions and a steady increase in the number of authors from outside Australia or New Zealand.